2018
DOI: 10.3390/cryst8120450
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Society of Automotive Engineers Regular Curved Retroreflector for Enhancing Optical Efficiency and Working Area

Abstract: A highly efficient regular curved retroreflector is proposed to meet the requirements of the US Society of Automotive Engineers (SAE) regulations. It is demonstrated that 28% higher retroreflection efficiency and 33% more working area can be accomplished with the new designed retroreflector when compared with the commercial ones used in modern vehicles.Based on pin-bundling technology, the tooling of a reflex reflector mold can be produced, and it can serve as a testing sample or for mass production. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…ese coordinates are defined in Figure 8, and the optimization process flowchart is shown in Figure 9. During the optimization process, the optimization object function f was established by a genetic algorithm and is given by [22,27]…”
Section: Design Of Freeform-surfaced Luminairementioning
confidence: 99%
See 1 more Smart Citation
“…ese coordinates are defined in Figure 8, and the optimization process flowchart is shown in Figure 9. During the optimization process, the optimization object function f was established by a genetic algorithm and is given by [22,27]…”
Section: Design Of Freeform-surfaced Luminairementioning
confidence: 99%
“…e luminaire mounting height, street light spacing, luminaire inclination angle, and road surface properties are essential for ensuring the desired street lighting performance, measured in terms of the average road surface brightness, brightness uniformity, longitudinal brightness uniformity, and threshold increment (glare factor) [1][2][3]20]. Furthermore, though the use of lightemitting diode (LED) technology requires less energy consumption and can provide longer-lasting lighting than conventionally used discharge lamps [21][22][23][24], there remain several disadvantages to the use of LED lights, such as their higher cost, unpredictable lifetime, and excess blue/white glare for human eyes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high tolerance to the direction of incident waves [10][11][12] retroreflectors have been used extensively in many applications instead of plane mirrors [13]. For instance, regular reflex reflectors [14][15][16], as shown in Figure 1a, can diverge the reflected energy into multiple light beams with equal emitting angle intervals [17][18][19], and these are currently the most commonly used retro-reflecting devices for vehicles [20,21]. In contrast to regular reflex reflectors, SuperPin reflex reflectors not only reflect light beams but also concentrate them to amplify the light intensity of signals for observers, as shown in Figure 1b [22].…”
Section: Introductionmentioning
confidence: 99%
“…The formula of retro-reflected light by (a) the EU Economic Commission for Europe (ECE) regular in ([16],Figure 1), (b) the ECE SuperPin in ([24],Figure 1), and (c) the ECE and US Society of Automotive Engineers (SAE) SuperPin Plus reflex reflector, an extension of SuperPin[24].…”
mentioning
confidence: 99%
“…In the fourth paper, Le et al [4] proposes a design of a curved retroreflector for enhancing optical efficiency and working area. By taking the advantages of compact size and high brightness of LED, this designed retroreflector does not only meet the requirements of the US Society of Automotive Engineers (SAE) regulations but also can be demonstrated that 28% higher efficiency and 33% more working area.…”
mentioning
confidence: 99%